Using Corporate Social Responsibility as Insurance for Financial Performance - Peloza, John (California management review, 2006)
This article provides a framework for simultaneously assessing the affirmative and defensive functions of Corporate Social Responsibility. It is based on integrating two traditionally distinct approaches to CSR: one views it as compatible with economic objectives, while the other regards it as incompatible with them. By bringing these two approaches together and recognizing CSR's multiple functions, this article analyzes how CSR can offer a crucial advantage to managers by providing a means of insuring financial performance against negative events. This latent insurance value is often ignored in traditional evaluations of the relationship between CSR and financial performance.